A Brief Review on the Development of Novel Potentially Active Azetidin-2-ones Against Cancer - da Silveira Pinto, Ligia S.; Vasconcelos, Thatyana R. Alves; Gomes, Claudia Regina B.; de Souza, Marcus Vinícius N. (Current Organic Chemistry, 2020)
Azetidin-2-ones (β-lactams) and its derivatives are an important group of heterocyclic compounds that exhibit a wide range of pharmacological properties such as antibacterial, anticancer, anti-diabetic, anti-inflammatory and anticonvulsant. Efforts have been made over the years to develop novel congeners with superior biological activities and minimal potential for undesirable side effects. The present review aimed to highlight some recent discoveries (2013-2019) on the development of novel azetidin-2-one-based compounds as potential anticancer agents.
Keywords: drugs